2021
DOI: 10.3389/fgene.2021.721258
|View full text |Cite
|
Sign up to set email alerts
|

COL3A1 and MMP9 Serve as Potential Diagnostic Biomarkers of Osteoarthritis and Are Associated With Immune Cell Infiltration

Abstract: BackgroundOsteoarthritis (OA) is one of the most common age-related degenerative diseases. In recent years, some studies have shown that pathological changes in the synovial membrane occur earlier than those in the cartilage in OA. However, the molecular mechanism of synovitis in the pathological process of OA has not been elucidated. This study aimed to identify novel biomarkers associated with OA and to emphasize the role of immune cells in the pathogenesis of OA.MethodsMicroarray datasets were obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…In this study, we detected those macrophages and most other immune cells were highly infiltrated in the OA synovium. Previous histology-based studies have also demonstrated macrophage enrichment in OA ( 28 , 29 ). Due to their essential roles in immune recruitment, inflammatory damage, and ECM degradation, macrophages have received much attention and are thought to be important lesion driver immune cells in OAs.…”
Section: Discussionmentioning
confidence: 77%
“…In this study, we detected those macrophages and most other immune cells were highly infiltrated in the OA synovium. Previous histology-based studies have also demonstrated macrophage enrichment in OA ( 28 , 29 ). Due to their essential roles in immune recruitment, inflammatory damage, and ECM degradation, macrophages have received much attention and are thought to be important lesion driver immune cells in OAs.…”
Section: Discussionmentioning
confidence: 77%
“…These results implied that silencing of COL3A1 suppressed malignant behaviors of TNBC. On the other hand, COL3A1 upregulation has been validated to facilitate immune evasion in cancers (Fang et al, 2021; Li et al, 2021). In this study, we observed the suppressive effect of COL3A1 knockdown on immune evasion in MDA‐MB‐231 and BT‐549 cells, as evidenced by increased LDH release and the percentage of CD8 + T cells along with reduced apoptosis rate of CD8 + T cells and the protein level of PD‐L1.…”
Section: Discussionmentioning
confidence: 99%
“…Module C was also critical, and six upregulated genes including COL5A2, COL5A1, COL3A1, COL1A1, COL1A2, and PCOLCE were found in Module C. A previous study indicated that COL5A1 was involved in the OA synovium elevation of collagens and cross-linking enzymes ( Tsezou, 2014 ). One previous study showed that COL3A1 may be a potential diagnostic biomarker for OA ( Li et al, 2021 ). Another study demonstrated that the expression levels of COL1A1 and COL5A1 were significantly upregulated in OA ( Zhu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%